MODERN GRAPHIC DESIGN PROMOTING ARCHAEOLOGICAL ARTIFACTS AND SCIENTIFIC TEXTS - Skourlis, Stelios (Design/Arts/Culture, 2020)
One of the most demanding and intriguing duties of the art of graphic design is the promotion of not only archaeological artifacts but scientific texts, as well. The skills and cognitive dexterities of the stakeholders involved in these projects exceed by far the common process of graphic designing. A most essential prerequisite is the experience which is based on a deep insight of Typography, Photography, Color Management, Graphic Design, good aesthetics, history and the perception to distinguish and pinpoint the unique artistic value of each and every artifact. So far, the study of archaeological artifacts appeared to be the exclusive right solely of archaeologists, but it is of utter importance that graphic designers, illustrators and photographers follow suit, since the promotion and the design process of a book or an application, is their field of study, as well. The entire process presupposes the ability to combine and unify modern typography, design elements, high quality photographs with newly-discovered artifacts that carry thousands of years of history. The daily process and collaboration with archaeologists is of most vital in order for the project to be successful. The parameters to be considered for just a single artifact, or a brief scientific paper referring to a brief historical period or a timeline are countless, some of which being the historical era, the civilization, the script style, language, religion, religious references and the like.